Exploring Students’ Cognitive Experiences in Reading and Listening: A Phenomenological Study - Puspita Maharani; Nabila Zuhairya; Yani Lubis (Jurnal Ilmiah Multidisiplin, 2026)
Reading and listening comprehension are essential skills in language learning that involve complex cognitive processes such as attention, working memory, inference-making, monitoring, and meaning construction. This phenomenological study aims to explore the cognitive experiences of final-year students in the English Education program during reading and listening activities. Through semi-structured interviews and written reflections, this study reveals students’ awareness of the cognitive processes they undergo, cognitive challenges such as limited working memory and unfamiliar vocabulary, as well as cognitive and metacognitive strategies ued to overcome these difficulties. Additionally, emotional experiences accompanying the cognitive processes, including frustration and satisfaction, were analyzed. The findings highlight the close relationship between cognitive and emotional aspects in language comprehension and suggest important implications for developing more effective and responsive reading and listening instruction. Further research with larger participant samples and diverse methodologies is recommended to enrich the findings.